Enhanced oxygen reduction at Pd catalytic nanoparticles dispersed onto heteropolytungstate-assembled poly(diallyldimethylammonium)-functionalized carbon nanotubes - Wang, D.; Lu, S.; Kulesza, P.; Chang, M.L.; De Marco, Roland; Jiang, San Ping (Royal Society of Chemistry, 2011)
Both Keggin-type phosphotungstic acid (HPW) and Pd are not prominent catalysts towards the oxygen reduction (ORR), but their composite Pd-HPW catalyst produces a significantly higher electrochemical activity for the ORR in acidic media. The novel composite catalyst was synthesized by self-assembly of HPW on multi-walled carbon nanotubes (MWCNTs) via the electrostatic attraction between negatively charged HPW and positively charged poly(diallyldimethylammonium (PDDA)-wrapped MWCNTs, followed by dispersion of Pd nanoparticles onto the HPW–PDDA–MWCNT assembly. The as-prepared catalyst was characterized by transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, thermal gravimetric analysis (TGA), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS).TEM images show that Pd nanoparticles were uniformly dispersed on the surface of MWCNTs even when the Pd loading was increased to 60 wt%. Electrochemical activity of the catalysts for the ORR was evaluated by steady state polarization measurements using a rotating disk electrode. Compared with the acid treated MWCNTs, Pd nanoparticles supported on the HPW-assembled MWCNTs show a much higher ORR activity that is comparable to conventional Pt/C catalysts. The high electrocatalytic activities could be related to high dispersion of Pd nanoparticles as well as synergistic effects originating from the high proton conductivity of HPW. The Pd/HPW–PDDA–MWCNTs system as the cathode catalyst in proton exchange membrane fuel cells is demonstrated.